MATHEMATICAL MODELLING OF DEHYDRATOR DRYING ON APPLE FRUIT SLICES - Indah Yuliasih; Dzulkifli Rasyid; Niken Ayu Permatasari (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
This research was conducted in order to evaluate the drying prosess using the Moisture Ratio (MR) drying model approach among Newton, Page, Henderson-Pabis and Midili. The thin-layer drying experiment was carried out in a Wirastar FDH10 food dehydrator at the constant temperature of 60°C for 23 h. The main responses, i.e, weight loss, moisture content and water activity (aw) were measured during the process. All data analysis and mathematical modeling was executed with the Microsoft Excel Analysis Tools Solver Add-In. The final weight of the dried apple slices was decreased by 80.2%, and a target moisture content in the range of 6–8% with a final water activity value of aw = 0.431 was also obtained. Comparing the models, Midili model turned to be the most adequate for describing these data as it presented the highest value of R2 =0.9804 and low values for SSE and RMSE. The empirical equation for the Midili model was MR = 1.000 exp(-0.342* ) + 0.0038*t. The model was validated which showed a good agreement, and the necessary time to dry from 84.4% on wet basis to 6.4% on wet basis is predicted at 11.5 h. This is a 42.5% increase in the time effectivity, which presents definite progress. Keywords: apple slices, drying model, moisture ratio, thin layer drying